Assessing sugar intake rapidly – a short form of the Marburg Sugar Index (MSI) - Margraf-Stiksrud, Jutta; Pieper, Klaus; Deinzer, Renate; Justus Liebig University Giessen (My University, 2023)
Background: Sugar intake is a major nutritional factor in the development of dental caries. To further clarify its contribution to oral health-related diseases, population-based investigations are recommended. To facilitate economic and reliable assessment of sugar intake, a short form of the approved Marburg Sugar Index (MSI) was developed. Methods: According to the principles of item reduction based on original data, a six-item-short form was constructed. A total of 468 participants (aged 15–81) answered the short form together with the long form in a counterbalanced cross-over design, and with two questionnaires concerning self-efficacy and decisional balance in oral health to verify construct validity. Results: Comparable item characteristics to the original MSI and a high correlation with the long form prove the usefulness of the short form, which was processed by the participants in less than one minute. Low correlations to the other two constructs show discriminant validity. Conclusion: The new short form of the MSI (MSI-S) can replace the long form, especially in population-based studies with no restrictions on assessment quality but with sufficient time saved to add other variables necessary to explore oral health-related issues.
Keywords: ddc:150